Why pay NGOs to involve the community? - Burger, Ronelle; Dasgupta, Indraneel; Owens, Trudy (Wiley, 2015)
We examine the case for donors providing financial incentives to, i.e. subsidizing, NGOs to increase community participation. We show that the introduction of such a ‘participation subsidy’ may reduce beneficiary welfare. Thus, eliminating community participation from the set of conditions for funding an NGO may in fact benefit target communities. We show how our theoretical analysis may be operationalized by applying it to data from the NGO sector in Uganda. Our empirical findings appear to reject the case for providing a participation subsidy in that context.